174k views
4 votes
Solve the system of equations:
y = 3x
y=x2-4

User Nicks
by
4.6k points

2 Answers

3 votes

Answer:

y=12 x=4

Explanation:

I will be using the elimination method to solve this

*2 y= 3x

*3 y= 2x-4.

2y= 6x

- 3y= 6x-12

-1y= -12. y= 3x

/-1 /-1. 12= 3x

y=12. /3 /3

4=x

User EngrStudent
by
5.3k points
1 vote

Answer:

x = -4

y = -12

Explanation:

Since y is 3x,

3x = 2x - 4

On solving we get x as -4

Substitute x and we get y as -12

User Keepyourliberty
by
4.8k points